ChemInform Abstract: Preparation of 2‐Phenyl‐3‐hydroxyquinoline‐4(1H)‐one‐5‐carboxamides as Potential Anticancer and Fluorescence Agents. Issue 41 (October 2015) - Funk, Petr; Motyka, Kamil; Dzubak, Petr; Znojek, Pawel; Gurska, Sona; Kusz, Joachim; McMaster, Claire; Hajduch, Marian; Soural, Miroslav
Abstract The title compounds are synthesized in order to study their properties compared to analogical 6‐8 carboxamide isomers.